2020
DOI: 10.1016/j.parepi.2019.e00131
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Blastocystis and parasitic archamoebids encountered in untreated wastewater samples by amplicon-based next-generation sequencing

Abstract: BackgroundApplication of next-generation sequencing (NGS) to genomic DNA extracted from sewage offers a unique and cost-effective opportunity to study the genetic diversity of intestinal parasites. In this study, we used amplicon-based NGS to reveal and differentiate several common luminal intestinal parasitic protists, specifically Entamoeba, Endolimax, Iodamoeba, and Blastocystis, in sewage samples from Swedish treatment plants.Materials and methodsInfluent sewage samples were subject to gradient centrifugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…Nevertheless, our finding of the avian subtypes ST6 and ST7 in humans as well as ST5 (often found in pigs) and ST8, could reflect cases of zoonotic transmission (Stensvold and Clark, 2016a ). Interestingly, rats might play a role in spreading of Blastocystis ST1-ST4 and possible also of ST8 as suggested by a study focused on a survey of wastewater samples in Sweden (Stensvold et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our finding of the avian subtypes ST6 and ST7 in humans as well as ST5 (often found in pigs) and ST8, could reflect cases of zoonotic transmission (Stensvold and Clark, 2016a ). Interestingly, rats might play a role in spreading of Blastocystis ST1-ST4 and possible also of ST8 as suggested by a study focused on a survey of wastewater samples in Sweden (Stensvold et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the presence of ST8 in fish samples might be related to local water contamination by animal or human wastes. In a recent study conducted in central/southern Sweden [35], ST8 was surprisingly identified in almost 40% of the untreated wastewater samples tested. However, as discussed by the authors, the host, whether human or animal, contributing to the sewage influent remains as yet unidentified.…”
Section: St Distribution Of Blastocystis Sp In Edible Marine Fishmentioning
confidence: 94%
“…Genomic DNAs extracted from the mouthwash samples were subject to microbiota profiling (metabarcoding), using the recently described 16S + 18S assay in place at Statens Serum Institut [16][17][18]. Briefly, PCR used one primer pair targeting the 16S (341F3/ 806R5 [5ʹ-ACT CCT AYG GGR BGC ASC AG-3ʹ/5ʹ-AGC GTG GAC TAC NNG GGT ATC TAA T-3ʹ]) and three primer pairs targeting the 18S (G3F1/ G3R1 [5ʹ-GCC AGC AGC CGC GGT AAT TC-3ʹ/5ʹ-ACA TTC TTG GCA AAT GCT TTC GCA G-3ʹ], G4F3/G4R3 [5ʹ-CAG CCG CGG TAA TTC CAG CTC-3ʹ/5ʹ-GGT GGT GCC CTT CCG TCA AT-3ʹ], and G6F1/G6R1 [3ʹ-TGG AGG GCA AGT CTG GTG CC-3ʹ/5ʹ-ACG GTA TCT GAT CGT CTT CGA TCC C-3ʹ]).…”
Section: Oral Microbiota Profilingmentioning
confidence: 99%